Cardiovascular Disease Risk Factors by BMI and Age in United States Firefighters. Issue 7 (31st May 2021) - Bode, Emilie D.; Mathias, Kevin C.; Stewart, Donald F.; Moffatt, Steven M.; Jack, Kepra; Smith, Denise L.
Abstract : Objective: This study examined cardiovascular disease risk factors by BMI category in firefighters, the association of BMI and age with risk factor prevalence, and the prevalence of risk factors by BMI category within age groups. Methods: Cardiovascular measures from the medical evaluations of 4, 453 firefighters, performed between 2015 and 2018 at four occupational health clinics in the United States (South‐West Cohort, Mid‐Atlantic Cohort, South‐East Cohort, and Mid‐West Cohort), were analyzed cross‐sectionally by BMI and age categories. Results: Among female firefighters with normal weight, 25% had high blood pressure, 8% had low high‐density lipoprotein cholesterol, and 0% had high glucose, whereas the prevalence in female firefighters with obesity was 57%, 45%, and 11%, respectively. Among male firefighters, there were independent and significant associations of BMI and age for the prevalence of high blood pressure, high cholesterol, high triglycerides, and high glucose. Higher BMI category was associated with a higher prevalence of high blood pressure, high triglycerides, and low high‐density lipoprotein cholesterol within all age groups and with a higher prevalence of high glucose and high cholesterol within ages 40 to 49 and 50 to 59 years. Conclusions: An increasing prevalence of risk factors with older age and higher BMI suggests that preventive strategies should be initiated in younger firefighters and aggressively promoted or mandated throughout firefighters' careers.